Evaluation of saddle height in elite cyclists - Mauch, M.; Goesele, A. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Proper bike fit is essential to prevent injuries and improve performance. Especially recreational cyclists, often short on experience, rely on professional adjustment for seating position. Common bike fitting methods use formulas based on rider anthropometrics, e.g. the LeMond method (pubic symphysis height [PSH] x 0.883) (LeMond, 1988) or the Hamley method (PSH x 1.09) (Hamley et al., 1967). Pruitt (2006) recommends the correct saddle height [SH] within a knee angle [KA] of 25-35°. The purpose of this study is to verify these methods in elite men and women cyclists for today`s application.